Study guides

☆☆

Q: What is -5x plus 13 equals -12?

Write your answer...

Submit

Still have questions?

Related questions

5x+49 = 8x+13 49-13 = 8x-5x 36 = 3x x = 12

-13 Plug 5 in and multiply it by -5 which equals -25 12 - 25 = -13

The answer to the math problem of 5x plus 12 equals 93-4 is 77/5.

5x - 4x = 13 - 3 ie x = 10

2x-12

5x + 3 = -12 5x =-12-3 =-15 x = -3

If 5x plus 3y equals 13, the x equals 2 and y equals 1. This is because 5x2=10 and 3x1=3, and 10+3=13.

8(1+5x) +5 = 13+5x => 8+40x + 5 = 13 +5x => 13+40x = 13+5x => 13-13+40x = 13-13+5x => 40x = 5x => 40x - 5x = 0 => 35x = 0 => 35x/35 = 0/35 => x = 0

Here is the work for that problem: 5x+ 2=12 5x= 12-2 5x=10 x= 2

No.

3x+7=5x-13 ----> 3x-5x=-13-7 ----> -2x=-6 -----> x=3

x = -5

x=12

3x - 7 = 5x + 13-2x = 20x = -10

If: 3x-7 = 5x+13 Then: x = -10

5x+12 = 4x-88 x = -100

x=-3

X=10.

3x - 7 = 5x + 133x - 5x = 13 + 7-2x = 20x = -10x=-3

88=13+5x -13 -13 75= 5x 75/5 =15 x=15

[5x+13]

(3, -4)

x = 12

slope = -1

y = 2x -1 y = 5x -13 So: 5x -13 = 2x -1 5x -2x = 13 -1 3x = 12 x = 4 and by substituting y = 7